THE ANNUAL CO2 EMISSIONS AND ENERGY COSTS OF DIFFERENT EXTERIOR WALL STRUCTURES IN RESIDENTIAL BUILDINGS IN TÜRKİYE - Ucar, Aynur (Turkish Soc Thermal Sciences Technology, 2024)
Carbon dioxide emissions are one of the most important causes of global climate change. It is accepted in the world today that the world urgently needs to reduce carbon dioxide emissions in order to avoid the worst impacts of climate change. In this study, the optimum thickness of each insulation material is determined depending on the available costs and the total annual CO2 emissions of insulation materials for building external walls with different structure in the selected cities from different climate regions of Turkey. The different wall types insulated with four different insulation materials are presented. The results indicate that the optimum insulation thickness varies from 2.5 to 13 cm and is different for each wall type and insulation material. The total annual CO2 emission per unit area of the wall varies between 3.32 and 10.32 kg CO2/m2 depending on the insulation material and wall type.
TÜRKİYE'DE KONUTLARDA FARKLI DIŞ DUVAR YAPILARININ YILLIK CO2 EMİSYONLARI VE ENERJİ MALİYETLERİ
Keywords: CO2 emissions; life cycle cost; Optimum insulation thickness; Eco-efficiency